Influence of Parity and Index Child Factors on Adoption of Exclusive Breastfeeding by Nursing-Mothers in Imo State Nigeria - S.N.O, Ibe; O, Obasi; E.A, Nwoke; C.R, Nwufo; C.I.C, Ebirim; E.O, Osuala; C.O, Amadi; C.O, Ezenwuba (International Journal of Medical and Health Sciences Research, 2017)
This study determined the influence of nursing-mothers’ parity and index child factors on adoption of exclusive breastfeeding practice by rural nursing-mothers in Imo State Nigeria. Nigeria has only 13% compliance to exclusive breastfeeding practice, hence the need for this study that employed descriptive survey design to obtain information from 340 nursing mothers from three selected communities in the state. The target population of the study was all the 405 nursing-mothers with children aged twenty-four months and below in the selected communities but 340 nursing-mothers responded. Instruments for data collection were structured questionnaire and Focus Group Discussion (FGD). Reliability of the instrument was established and r = 0.8. Ten nursing mothers from each of the communities participated in FGD. Results of the study revealed that exclusive breastfeeding practice was 13.5% in the target communities. Only parity, place of ante-natal care and place where the child was delivered were statistically significant (P<0.05). The study concluded that parity and type of facility attended for ante and natal care played a role in the adoption of exclusive breastfeeding practice. There is need to strengthen maternity facilities to render effective exclusive breastfeeding promotion, and also to follow up mothers in the community.